An Immunogenic Cell Death-Related Classification Predicts Prognosis and Response to Immunotherapy in Head and Neck Squamous Cell Carcinoma - Wang, Xinwen; Wu, Shouwu; Liu, Feng; Ke, Dianshan; Wang, Xinwu; Pan, Dinglong; Xu, Weifeng; Zhou, Ling; He, Weidong (Frontiers in Immunology, 2021)
Immunogenic cell death (ICD) has been classified as a form of regulated cell death (RCD) that is sufficient to activate an adaptive immune response. Accumulating evidence have demonstrated the ability of ICD to reshape the tumor immune microenvironment through the emission of danger signals or DAMPs, which may contribute to the immunotherapy. Currently, identification of ICD-associated biomarkers that stratify patients according to their benefit from ICD immunotherapy would be of great advantage. Here, we identified two ICD-associated subtypes by consensus clustering. ICD-high subtype was associated with the favorable clinical outcomes, abundant immune cell infiltration, and high activity of immune response signaling. Besides, we established and validated an ICD-related prognostic model that predicted the survival of HNSCC and was associated with tumor immune microenvironment. In conclusion, we established a new classification system of HNSCC based on ICD signatures. This stratification had significant clinical outcomes for estimating prognosis, as well as the immunotherapy of HNSCC patients